On the crashworthiness performance of thin-walled energy absorbers: Recent advances and future developments - Baroutaji, Ahmad; Sajjia, Mustafa; Olabi, Abdul-Ghani (Thin-walled structures, 2017)
Over the past several decades, a noticeable amount of research efforts has been directed to minimising injuries and death to people inside a structure that is subjected to an impact loading. Thin-walled (TW) tubular components have been widely employed in energy absorbing structures to alleviate the detrimental effects of an impact loading during a collision event and thus enhance the crashworthiness performance of a structure. Comprehensive knowledge of the material properties and the structural behaviour of various TW components under various loading conditions is essential for designing an effective energy absorbing system. In this paper, based on a broad survey of the literature, a comprehensive overview of the recent developments in the area of crashworthiness performance of TW tubes is given with a special focus on the topics that emerged in the last ten years such as crashworthiness optimisation design and energy absorbing responses of unconventional TW components including multi-cells tubes, functionally graded thickness tubes and functionally graded foam filled tubes. Due to the huge number of studies that analysed and assessed the energy absorption behaviour of various TW components, this paper presents only a review of the crashworthiness behaviour of the components that can be used in vehicles structures including hollow and foam-filled TW tubes under lateral, axial, oblique and bending loading. •Researches on energy absorption behaviour of hollow tubes are reviewed.•An overview is given on the crashworthiness behaviour of foam-filled tubes.•Studies on the crashworthiness design and optimisation are summarised.•Crashworthiness topics that require further developments are identified.